(untitled) (ModaPalavra e-periódico, 2020)
In recent historiography, there is a consensus that the modernizing reforms promoted in Rio de Janeiro at the beginning of the 20th century have changed the capital’s architecture and the relationship between its population and the urban experience, introd ucing new practices into daily lives of cariocas. Among them was the introduction of sports, with the press being the main vehicle for its dissemination. This article explores the presence of fashion dedicated to sports in chronicles and examines its contr ibution to the validation of a collective imagination about leisure. The literary representation of sportswear gains complexity in the “ civilisation du journal ” , in which social relations are regulated by the production and reading of magazines. Therefore, the aim is to map out the access to fashion paradigms by readers of periodicals. As a case study, two chronicles of João do Rio on the sports theme are analyzed. Published in the column “ A Semana Elegante ” in 1916, they focus on the female presence and th eir clothing in the practice of tennis and sea bathing. We conclude that the importation and representation of sports practices and their fashion acted in the construction of an imaginary of elegance in the city of Rio de Janeiro.